Establishing the Reliability and Validity of Measurements of Walking Time Using the Emory Functional Ambulation Profile - Wolf, Steven L; Catlin, Pamela A; Gage, Katherine; Gurucharri, Karen; Robertson, Renee; Stephen, Kathleen (Physical therapy, 1999)
Background and Purpose. The Emory Functional Ambulation Profile (E-FAP) measures time to walk in different environments and accounts for use of assistive devices. This study assessed the reliability and validity of walking time measurements using these components. Subjects. Twenty-eight subjects who had strokes and 28 subjects without impairment were recruited. Methods. The E-FAP, Berg Balance Test, Functional Reach Test, and Timed 10-Meter Walk Test were administered in random order during a single data collection session. Results. Interrater reliability for the total E-FAP was ≥.997. Subjects without impairment performed better on all 4 tests than did subjects who had strokes. Increased times on the E-FAP correlated with poor performance on the Berg Balance Test and slow gait speeds on the Timed 10-Meter Walk Test in the subjects who had strokes. The E-FAP scores and the Functional Reach Test scores were not correlated. Conclusion and Discussion. The E-FAP can be administered easily and inexpensively. Because the E-FAP scores differentiated subject groups and correlated with known measures of function, the E-FAP may be a clinically useful measure of ambulation.